Research on Factors Affecting the Reducer Transmission Efficiency of Electric Vehicles - Feng Chen; Weilin Li; Yinda He; Zhongjie Zhang; Lü Binghai; Qinghua Yang (Jixie chuandong)
The transmission efficiency of the reducer is the main factor affecting the efficiency of the whole transmission system. Establishing the transmission efficiency model and analyzing the influencing factors on transmission efficiency are of great significance to improve the transmission efficiency of electric vehicles. According to the characteristics of electric vehicle reducer， four transmission efficiency loss factors including gear meshing loss， bearing loss， oil stirring wind resistance loss and oil seal loss are analyzed and the transmission efficiency calculation model is established. The lubricant， speed and torque are developed. The effects of oil， speed and torque on the transmission efficiency of single gear two-stage reducer for electric vehicles are studied theoretically. A high-speed three-axis comprehensive performance test bench is built and the orthogonal experimental research on the precision of an established model and the influencing factors of transmission efficiency are performed. The theoretical and experimental research results show that： the maximum relative error of the established model is -0.59%， which is less than that of ISO/TR 14179—1：2001 （-1.75%）； as the speed increases， the transmission efficiency gradually decreases； the speed has the greatest influence on transmission efficiency； as the torque increases， the transmission efficiency gradually increases； the lower the lubricating oil temperature is， the lower the transmission efficiency becomes； the influence of the lubricating oil grade on the transmission efficiency is not obvious； the lower the lubricating oil viscosity is， the higher the transmission efficiency becomes and the oil has the least influence on transmission efficiency.